Eletrossíntese de nanoestruturas de polianilina - Xavier, Miguel Gustavo (Universidade Federal de São Carlos, 2010)
The potentiodynamic and potentiostatic electrochemical synthesis were performed for the eletrosynthesis of nanofibers and nanoparticles of polyaniline on gold electrodes without the use of physical or chemical templates. The electrochemical system used is composed of aniline and hydrochloric acid and the formation of PANI nanostructures was by analyzed by the following parameters: scan rate, concentration of monomer; potential interval; number of cycles, temperature and pH. The films of PANI were characterized by an electrochemical technique (voltammetry cyclic), two microscopic techniques (electron microscopy scanning and atomic force microscopy) and a spectroscopic technique (UV-Vis absorption). It was conducted the study of the influence of the number of cycles in the oxidation state of the polyaniline film and the comparison between models of nucleation and growth of metals with the process of formation of polyaniline nanoparticles. The studies have demonstrated that the variation on the concentration of monomer, the electrochemical technique used in eletrosynthesis, temperature and pH are fundamental steps to determine the morphology of polyaniline. The comparison of theoretical models of nucleation and growth metals with the formation of polyaniline nanoparticles showed a good correlation with instantaneous nucleation with two-dimensional growth.
Keywords: Eletroquímica; Polianilina; Nanofibras; Nanopartículas; Síntese potenciostática; CIENCIAS EXATAS E DA TERRA::QUIMICA